Service quality in health and wellness tourism: Trends in Portugal - Quintela, Joana (2019)
The purpose of this study was to: a) analyze the impact of service quality on client satisfaction; b) identify travel behavior and c) assess the attributes that are more important and more satisfaction-oriented from the client point of view. These objectives are designed to provide health and wellness tourism units with a better understanding of the market; help them match supply to the needs, wishes and attitudes of their target markets and draw up improved plans for developing their potential. The empirical data, collected in five Portuguese hot springs units, was evaluated using a modified SERVQUAL scale. Attributes designated as more pleasing, and those receiving more emphasis, were assessed through the Importance-Performance-Analysis model. Travel behavior was assessed by means of a purpose-made questionnaire. In terms of service quality, we confirmed that aspects relating to attendance ("ability of the employee to perform accurately and dependably", "employee's willingness to help the customer and provide prompt service", "capacity to provide individualized attention") were more satisfying for users of these units. Through the IPA, we established that the attributes of "quality / price ratio"; "quality of complementary services (lodging and leisure)"; and "geographic location (quality of transport and accessibility)" offered were of less interest to clients. Implications for Portugal were discussed.